2009
DOI: 10.1037/a0015409
|View full text |Cite
|
Sign up to set email alerts
|

Setting goals to switch between tasks: Effect of cue transparency on children’s cognitive flexibility.

Abstract: Three experiments examined the difficulty of translating cues into verbal representations of task goals by varying the degree of cue transparency (auditory transparent cues, visual transparent cues, visual arbitrary cues) in the Advanced Dimensional Change Card Sort, which requires switching between color-and shape-sorting rules on the basis of cues. Experiment 1 showed that 5-and 6-year-old children's performance improved as a function of cue transparency. Experiment 2 yielded the same pattern of results and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
142
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 117 publications
(163 citation statements)
references
References 94 publications
16
142
0
3
Order By: Relevance
“…This demonstrates the importance of cue strength. Chevalier and Blaye (2009) reported a similar finding in older children : transparent verbal task cues elicited faster and more accurate responses than less transparent or arbitrary cues, on both switch and 'stay' trials. Thus, for children and adults, cue strength is as important or more important than flexibility in determining how people adapt to a series of problems.…”
Section: G E N E R a L Discussionsupporting
confidence: 61%
“…This demonstrates the importance of cue strength. Chevalier and Blaye (2009) reported a similar finding in older children : transparent verbal task cues elicited faster and more accurate responses than less transparent or arbitrary cues, on both switch and 'stay' trials. Thus, for children and adults, cue strength is as important or more important than flexibility in determining how people adapt to a series of problems.…”
Section: G E N E R a L Discussionsupporting
confidence: 61%
“…Goalsetting difficulties on paradigms such as the Advanced DCCS and the Shape School seem all the more probable as these paradigms use arbitrary cues that are difficult to translate into verbal representations of task goals. Consistent with this, 5-to-6-year-old children's performance has been shown to increase as a function of cue transparency on the Advanced DCCS even with no articulatory-suppression task (Chevalier & Blaye, 2009).…”
Section: Processes Contributing To Flexibilitysupporting
confidence: 57%
“…These results evidence that preschoolers' set-shifting difficulties result at least partially from goal-setting failures. In addition, a decreasing effect of cue transparency on accuracy-based mixing costs in 7-and 9-year-olds and adults (although they remained significant on RTs), suggests that set-shifting progress occurring at school age relates partially to increasingly efficient goal-setting skills (Chevalier & Blaye, 2009). Such goal-setting improvement is likely to be related to the increase in inner-speech efficiency that occurs during school age (e.g., Flavell et al, 1966), although direct evidence of this still needs to be reported.…”
Section: Processes Contributing To Flexibilitymentioning
confidence: 99%
See 1 more Smart Citation
“…One possibility is that children are able to generate potential tool-innovation solutions to the task, but find it difficult to move on from unsuccessful ideas, and so tend to become "stuck in set". The ability to select and switch between multiple perspectives, tasks or strategies to determine the optimal option for the current situation is a well-known component of executive function that develops significantly between 3 and 5 years (e.g., Diamond, 2006;Chevalier & Blaye, 2009). This is demonstrated in simple card-sorting tasks (Frye, Zelazo & Palfai, 1995;Espy, 1997), where children begin to demonstrate the ability to shift flexibly between rules.…”
Section: Why Do Childrenmentioning
confidence: 99%